Fundoscopic findings in pre-eclamptic and eclamptic patients Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2022)
In order to describe the fundoscopic findings in patients with pre-eclampsia and eclampsia hospitalized at the Hospital Central Universitario Dr. Antonio María Pineda during the period April-August 2020, a cross-sectional descriptive study was carried out with a sample of 25 patients whose diagnoses were mild and severe preeclampsia (44%, respectively), followed by eclampsia (12%). The mean age of the patients was 28.29 ± 9.08 years with mean gestational age of 35.8 ± 2.2 weeks; 60% had preterm pregnancies. The visual symptoms reported were blurred vision (32%), scotomas (24%), diplopia (8%) and amaurosis (4%); 64% had no visual symptoms. Visual acuity in the right eye was 20/20 (56%) and 20/30 (20%) and in the left eye was 20/20 (60%) and 20/25 (24%). Fundoscopic alterations found were decreased arteriolar reflex (16%), venular thickening, pathologic arterio-venular crossings and vascular tortuosity (12%, respectively) in both eyes. Grade I (32%), grade II (4%) and IV (4%) hypertensive retinopathy was found in both eyes. Grade I and III hypertensive retinopathy was found in the right eye (4% each) and in the left eye grade II (4%). When broken down by type of hypertensive disorder, mild preeclamptic patients presented grade I (27.2%) and IV (9%) hypertensive retinopathy, severe preeclamptic patients grade I (45.4%) and II (9%) and eclamptic patients only grade III (33.3%). Based on the results it can be concluded that the fundus oculi test proves to be a fundamental diagnostic tool in the management of patients with pre-eclampsia and eclampsia.